2004
DOI: 10.1111/j.1365-2133.2004.05850.x
|View full text |Cite
|
Sign up to set email alerts
|

Childhood linear IgA disease in association with autoimmune lymphoproliferative syndrome

Abstract: A child is described who had the signs of autoimmune lymphoproliferative syndrome from an early age and later developed a blistering dermatosis that was shown to be childhood linear IgA disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 15 publications
1
10
0
1
Order By: Relevance
“…7,11 Childhood LABD has been mostly associated with infections or drug ingestion and rarely with other conditions such as ulcerative colitis and autoimmune lymphoproliferative disease. 2,9 The most frequently reported drugs that can induce LABD in adults are antibiotics such as vancomycin, penicillin G, ampicillin, cefamandole, TMP-SMX, rifampin and sulfisoxazole, NSAID such as piroxicam, naproxen and diclofenac, interferon-gamma, interleukin-2, phenytoin, amiodarone, captopril, iodine contrast agent, somatostatin, lithium, furosemide and cyclosporine. 1,4,5 Drug-induced LABD is not as well documented in childhood as it is in adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…7,11 Childhood LABD has been mostly associated with infections or drug ingestion and rarely with other conditions such as ulcerative colitis and autoimmune lymphoproliferative disease. 2,9 The most frequently reported drugs that can induce LABD in adults are antibiotics such as vancomycin, penicillin G, ampicillin, cefamandole, TMP-SMX, rifampin and sulfisoxazole, NSAID such as piroxicam, naproxen and diclofenac, interferon-gamma, interleukin-2, phenytoin, amiodarone, captopril, iodine contrast agent, somatostatin, lithium, furosemide and cyclosporine. 1,4,5 Drug-induced LABD is not as well documented in childhood as it is in adults.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 LABD and chronic bullous disease of childhood are now considered to be a single entity. 3 The diagnosis of LABD is confirmed by detecting a linear band of IgA deposit at the basement membrane.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a case, as suspected in our patient, ALPS was associated with linear disease, an autoimmune subepithelial disorder characterized, at all ages from the first month of life, by onset of blisters on skin and mucosal membranes, pain and swallowing difficulties, raised serum IgA, and linear IgA deposits at the basement membrane zone. 24 Wu et al 25 reported on a case of lupus and lymphoproliferative disease, due to a FAS-ligand gene mutation and consequent FAS-ligand deficiency, with positive lupus test, raised T-cells after activation, normal CD4 -CD8 -T cells in blood (ALPS type 1b). Dianzani et al 26 reported on a series of male patients with a familial syndrome characterized by thrombocytopenia, enlarged lymph nodes and/or splenomegaly, neutropenia in which TCD4 -and TCD8 -cells were not expanded, PHA test was normal as in controls, and hyper γ-globulinemia (2 cases), hypo-γ-globulinemia (2 cases), and γ-globulinemia fluctuations (3) were present.…”
Section: Discussionmentioning
confidence: 99%
“…Lebensjahr auf und zeigt in der Regel einen selbstlimitierenden Verlauf. Bei der LAD wurden assoziierte Erkrankungen wie lymphoproliferative Syndrome [10] und Colitis ulcerosa [4] beschrieben. Paige et al berichten über eine Inzidenz der Colitis ulcerosa von 7,1% bei Patienten mit einer LAD [7], diese liegt somit bedeutend höher, als sie bei der Gesamtbevölkerung mit 0,2-0,5% angegeben wird [1,6].…”
Section: Diskussionunclassified